Education and Reform in China. - Hannum, E (Routledge, 2007)
Transformative market reforms in China since the late 1970s have improved living standards dramatically, but have also led to unprecedented economic inequality. During this period, China’s educational system was restructured to support economic development, with educational reforms occurring at a startling pace. Today, the educational system has diversified in structure, finance, and content; it has become more market-oriented; and it is serving an increasingly diverse student population. These changes carry significant consequences for China’s social mobility and inequality, and future economic prospects. In Education and Reform in China, leading scholars in the fields of education, sociology, demography, and economics investigate the evolution of educational access and attainment, educational quality, and the economic consequences of being educated. Education and Reform in China shows that economic advancement is increasingly tied to education in China, even as educational services are increasingly marketized. The volume investigates the varying impact of change for different social, ethnic, economic and geographic groups. Offering interdisciplinary views on the changing role of education in Chinese society, and on China’s educational achievements and policy challenges, this book will be an important resource for those interested in education, public policy, and development issues in China.